2010
DOI: 10.1093/gbe/evq007
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Human Microsatellites across 450 Million Years of Evolution

Abstract: The sequencing and comparison of vertebrate genomes have enabled the identification of widely conserved genomic elements. Chief among these are genes and cis-regulatory regions, which are often under selective constraints that promote their retention in related organisms. The conservation of elements that either lack function or whose functions are yet to be ascribed has been relatively little investigated. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 73 publications
5
52
0
Order By: Relevance
“…22 In contrast, we exploit the Drosophila melanogaster population data set to bridge the gap between SSR micro-and macro-evolution. This gap will shrink further with additional genome sequences being released in the near future, either from very closely related sister species or from separate populations of the same species.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…22 In contrast, we exploit the Drosophila melanogaster population data set to bridge the gap between SSR micro-and macro-evolution. This gap will shrink further with additional genome sequences being released in the near future, either from very closely related sister species or from separate populations of the same species.…”
Section: Discussionmentioning
confidence: 99%
“…Such an exponential decay has been observed as well for the conservation of human SSR loci in vertebrate genomes and may be a general trend in SSR macroevolution. 22 As mentioned before, SSR mutation rates are much lower in Drosophila than in vertebrates, and reduced mutation rates might partly be attributed to the facts that i) SSRs in D. melanogaster are shorter, 58 and ii) shorter SSRs are less mutable. 2,59 By applying the same SSR identification method used in this study for Drosophilidae to five mammal genomes (human, chimpanzee, mouse, rat, pig), we indeed found that Drosophila SSRs are shorter than mammalian SSRs (on average 26 nt vs. 32 nt; see Supplementary File 1 for details).…”
Section: Overall Macroevolutionary Trend Of Simple Sequence Repeatsmentioning
confidence: 92%
See 3 more Smart Citations